Lipohypertrophy Monitoring Study (LIMO): Effect of single use of 4 mm pen needles combined with education on injection site rotation on glycaemic control: Confirmation of an unpleasant truth. Issue 1 (29th September 2021) - Bochanen, Niels; Decochez, Katelijn; Heleu, Els; Cuypers, Joke; Vercammen, Chris; Coremans, Peter; Vanhaverbeke, Gerd; Shadid, Samyah; Keymeulen, Bart; Bolsens, Nancy; De Block, Christophe
Abstract: Aims: To investigate whether single use of 4 mm needles combined with education about injection technique and lipohypertrophy affects HbA1c, hypoglycaemia and glucose variability. Methods: Insulin‐injecting people with diabetes recruited from nine Belgian diabetes centres were prospectively followed for 6 months. They were provided 4 mm pen needles and education concerning injection technique using an online platform (BD and Me™) based on the international Forum for Injection Technique & Therapy Recommendations focused on avoidance of lipohypertrophy zones and reduction of needle reuse. Results: A total of 171 people with diabetes were included of which 146 completed the study. At baseline, lipohypertrophy was present in 63.0% of those who completed the study, with 51.4% injecting in zones of lipohypertrophy, 37.0% incorrectly rotating and 95.9% reusing needles. After the intervention, 7.5% still injected in a lipohypertrophy zone, 4.1% rotated incorrectly and needle reuse decreased to 21.2%. The number of participants with severe hypoglycaemias (from 15.8% to 4.1%, p  < 0.001), unexplained hypoglycaemias (from 46.6% to 16.4%, p  < 0.001) and high glucose variability (from 64.4% to 29.5%, p  < 0.001) was significantly reduced. HbA1c and total daily insulin dose remained stable. Conclusion: The combination of 4 mm pen needles and online education on injection techniques significantly reduced the number of people with severe hypoglycaemic episodes, unexplained hypoglycaemia and high glucose variability but did not improve HbA1c control nor lower insulin needs. Trial registration: ClinicalTrials.gov NCT04659330.